PERBANDINGAN CALORIFIC VALUE BERAGAM BAHAN BAKAR MINYAK YANG DIPASARKAN DI INDONESIA MENGGUNAKAN BOMB CALORIMETER - Ronaldo Irzon (Jurnal Geologi dan Sumberdaya Mineral, 2012)
Calorific value is amount of released energy when a known volume of gas is completely combusted. Now, the market of fuels in Indonesia is not only owned by Pertamina, but there have been many gas stations conducted by foreign companies since 2005. One of the most famous ways to rank the fuels' performance is based on research octane number (RON). A different kind of fuels' calorific value with various octane number sold in many gas stations would be important information for fuel customers. The use of the bomb calorimeter to analyze the calorific value has been published in diverse applications. Although bomb calorimeter is viable to measure the heat content of the liquid, we can not easily find a writing of using the equipment on this kind of sample. The method used here has been successful to measure the calorific values of three liquid samples using bomb calorimeter. This study quantifies calorific value of eight gasoline and five diesel samples of 83 measurements. Statistics measurements of at least six times repetition indicate: the method have very good stability (%RSD = 0.09 – 0.63%), there are differences in colorific value on samples with same octane number produced by different company, increase in octane number also raises the samples' calorific value, and the ratio of fuel's price to their heat content is still lame.Keywords : bomb calorimeter, calorific value, fuel, octane number